Teaching Basic Life Support for High School students: quasi-experimental study (Research, Society and Development, 2021)
Introduction: knowledge of Basic Life Support measures favors assistance in cardiopulmonary arrest, with a view to reducing the mortality rate. Objective: to analyze the effect of training in Basic Life Support for high school students. Methodology: quasi-experimental study, carried out in March 2019, in a federal public education institution, with high school students. Sociodemographic data and questions about knowledge in Basic Life Support were collected from a questionnaire previously validated by judges, which were later analyzed using the SPSS version 23.0 program. To compare the variable level of knowledge in the immediate post-test between the groups, the Mann-Whitney test was used and this same variable within the groups, in relation to the number of correct answers, was evaluated by the Wilcoxon test. Results: Basic Life Support training was effective in improving the level of knowledge, comparing the pre-test to the immediate post-test (p